Caracterización socioeconómica y productiva de la parroquia Guaytacama, cantón Latacunga, provincia de Cotopaxi 2022. - Cárdenas Vásconez, Emily Pamela (2022)
The objective of this research was socioeconomic and productive characterization of Guaytacama Parish through territorial data collection by random sampling. In order to carry out the activity, a 66- questionnaire was designed, including social, demographic, economic, service indicators and organizational productive characteristics. It was determined that 400 sample units would be collected from entire parish using the formula or sampling method of Martínez Bencardino (2012), and Kobo Toolbox software developed at Harvard University was used for survey. With obtained data, it was determined that in Guaytacama parish there is a predominance of females between 20 and 60 years old, most of them are considered mestizos, education level that they have is high school with 42%, 78% respondents have their own home, their income is obtained from their own businesses and sustain their houses economically is from agriculture. Families are made up by 3 to 4 members, which 16% of families with a disability person. About services quality terms, they have public transportation and the most used is bus with 48%. Fifty-nine percent of population considers water service as good quality, and water collection is twice a week. Fifty-six percent have had their homes burglarized. From surveyed inhabitants, 46% have agricultural production areas, which 33% have water for irrigation, mostly using a sprinkler system followed by gravity irrigation. The use that the families give to their land is for crops and animals (46%), 51% of producers mention that whole family is in charge of agricultural management, the crops commonly planted are (47%) and pasture (16%), 32% of the producers use their own seeds. On area of motivational support, the parish requires training for 22% on crop management, 21% about animal management and 13% on vegetable gardens.